Rethinking the Significance of Pesantren-Based Integrative Islamic Studies in the Faculty of Ushuluddin and Dakwah State Institute of Islamic Studies Kediri - Moh. Asror Yusuf (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
The Faculty of Ushuluddin and Dakwah State Institute of Islamic Studies Kediri is facing many challenges, one of which is related to the number of students, as it currently seems to be less interesting and irrelevant to the work field. Moreover, the Islamic Studies provided seems to be supplying insufficient capability for graduates compared with the pesantren alumni. Based on this statement, this paper seeks to find some proper solutions to suggest. This study examined the documents of this faculty, specifically related to the curriculum, and also interviewed the stakeholders. It was concluded that to maintain and develop the faculty’s existence, some changes were necessary. These solutions include strengthening the integration within Islamic studies by using a practical theology approach in teaching and learning, as well as continuously developing the ability of students to attain a higher order of thinking. The third solution was to give special attention to the pesantren-based primary Islamic literature, which was mostly delivered in Arabic, along with strengthening the students’ ability in understanding the language.